Important Aspects of Public Control in the Activities of Local Executive Bodies in the New Republic of Uzbekistan - Abdujabbarovna, Dadasheva Akida (International Journal of Law and Society, 2023)
The article is devoted to wide-ranging research, and the important aspects of public control in the activities of local executive bodies in Uzbekistan today, the normative and legal basis of the action, and the differences from the previously adopted legislation are analyzed. The purpose of the study is to identify problems and shortcomings in the system of public control over the activities of local executive bodies in the territory of the Republic of Uzbekistan. The article provides an analysis of the results of a sociological survey conducted on the legal, regulatory documents of public control of the activities of local executive bodies in the territory of the Republic of Uzbekistan. In addition, a retrospective analysis of the views of Western researchers and ancient Eastern thinkers, such as public opinion, justice, and the basis of civil society because of the control of society over power, is described. As a scientific innovation, differences were found between the legislation on public control adopted in Uzbekistan and several regulations and decisions adopted by the Cabinet of Ministers, the fact that they cover all processes and the duties and powers are returned, and the clearly defined sequence of tasks. As a result, in the conditions of New Uzbekistan, it was determined that it is necessary to improve the functions of representative bodies, develop the mechanisms of their implementation, and restore legal knowledge in higher education institutions.